2022
DOI: 10.1038/s41467-022-29856-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated photonic metasystem for image classifications at telecommunication wavelength

Abstract: Miniaturized image classifiers are potential for revolutionizing their applications in optical communication, autonomous vehicles, and healthcare. With subwavelength structure enabled directional diffraction and dispersion engineering, the light propagation through multi-layer metasurfaces achieves wavelength-selective image recognitions on a silicon photonic platform at telecommunication wavelength. The metasystems implement high-throughput vector-by-matrix multiplications, enabled by near 103 nanoscale phase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…5 b,c) is dominantly due to the local periodic approximation that is used in the numerical modeling. Locally periodic approximation is alternatively utilized in many numerical modeling of metasurface-optics 22 26 , 32 , 33 , because of large memory requirements of full-wave simulators. Also, the assumption of unit-transmission-amplitude for all meta-atom geometries along metalines can cause some small discrepancies between the two results (the reason that we mention “small discrepancies” is that the transmission amplitude of all meta-atoms is very near to 1).…”
Section: Resultsmentioning
confidence: 99%
“…5 b,c) is dominantly due to the local periodic approximation that is used in the numerical modeling. Locally periodic approximation is alternatively utilized in many numerical modeling of metasurface-optics 22 26 , 32 , 33 , because of large memory requirements of full-wave simulators. Also, the assumption of unit-transmission-amplitude for all meta-atom geometries along metalines can cause some small discrepancies between the two results (the reason that we mention “small discrepancies” is that the transmission amplitude of all meta-atoms is very near to 1).…”
Section: Resultsmentioning
confidence: 99%
“…The physical network is integrated with CMOS imaging sensors for miniaturized and portable sensing and computing all-in-one chip. Although there were also explorations of on-chip integration 26 , 52 , our architecture can be easily mass-produced because both CMOS chips and metasurfaces can be manufactured based on semiconductor processes. Another huge advantage of MDNN is the ability to fully exploit parallel operations of light by using the multiplexing of the metasurface.…”
Section: Discussionmentioning
confidence: 99%
“…This scheme has a simple structure design, and the manufacturing process is compatible with the CMOS process, which is convenient for large-scale and low-cost manufacturing. Similarly, in 2022, Gu et al experimentally fabricated and demonstrated this 1D multilayer diffractive metasurface system, which was fabricated on SOI substrates by one-step lithography and etching (Figure c). The demonstrated spatial pattern classifier in a two-layer metasystem achieves accuracies of 92% and 89% under narrowband continuous wave excitation and broadband femtosecond pulse excitation, respectively.…”
Section: Configurations For Ipnnsmentioning
confidence: 98%
“…Subwavelength structure manifested diffraction between metasurface layers (right). Reprinted with permission from ref . Copyright 2022 Springer Nature.…”
Section: Configurations For Ipnnsmentioning
confidence: 99%